Uncovering Potential Applications of Cyanobacteria and Algal Metabolites in Biology, Agriculture and Medicine: Current Status and Future Prospects - Singh, Rachana; Parihar, Parul; Singh, Madhulika; Bajguz, Andrzej; Kumar, Jitendra; Singh, Samiksha; Singh, Vijay P.; Prasad, Sheo M. (Frontiers in Microbiology, 2017)
Cyanobacteria and algae having complex photosynthetic systems can channelize absorbed solar energy into other forms of energy for production of food and metabolites. In addition, they are promising biocatalysts and can be used in the field of “white biotechnology” for enhancing the sustainable production of food, metabolites and green energy sources such as biodiesel. In this review, an endeavour has been made to uncover the significance of various metabolites like phenolics, phytoene/terpenoids, phytols, sterols, free fatty acids, photoprotective compounds (MAAs, scytonemin, s, polysaccharides, halogenated compounds, etc.), phytohormones, cyanotoxins, biocides (algaecides, herbicides and insecticides) etc. Apart from this, the importance of these metabolites as antibiotics, immunosuppressant, anticancer, antiviral, anti-inflammatory agent has also been discussed. Metabolites obtained from cyanobacteria and algae have several biotechnological, industrial, pharmaceutical and cosmetic uses which have also been discussed in this review along with the emerging technology of their harvesting for enhancing the production of compounds like bioethanol, biofuel etc. at commercial level. In later sections, we have discussed genetically modified organisms and metabolite production from them. We have also briefly discussed the concept of bioprocessing highlighting the functioning of companies engaged in metabolites production as well as their cost effectiveness and challenges that are being addressed by these companies.